Nature: a new paradigm for well-being and ergonomics - Richardson, Miles; Maspero, Marta; Golightly, David; Sheffield, David; Staples, Vicki; Lumber, Ryan (Taylor & Francis, 2016)
Nature is presented as a new paradigm for ergonomics. As a discipline concerned with well-being, the importance of natural environments for wellness should be part of ergonomics knowledge and practice. This position is supported by providing a concise summary of the evidence of the value of the natural environment to well-being. Further, an emerging body of research has found relationships between well-being and a connection to nature, a concept that reveals the integrative character of human experience which can inform wider practice and epistemology in ergonomics. Practitioners are encouraged to bring nature into the workplace, so that ergonomics keeps pace with the move to nature-based solutions, but also as a necessity in the current ecological and social context. Practitioner Summary: Nature-based solutions are coming to the fore to address societal challenges such as well-being. As ergonomics is concerned with well-being, there is a need for a paradigm shift in the discipline. This position is supported by providing a concise summary of the evidence of the value of the natural environment to well-being.